Peran Pustakawan dalam Perkembangan Perguruan Tinggi - S Manaf (Pascasarjana IAIN Metro, 2020)
The role of the Librarian, has progressed over time. Now librarians are not only serving the circulation of books, but are required to be able to provide information quickly, precisely, accurately, and efficiently in terms of time and cost. Librarians are required to develop competence in themselves in order to support the implementation of tertiary education programs. Competency and librarians play an important role in supporting the achievement of the vision of higher education. In this paper, it is explained and explained matters relating to the competence and role of librarians in supporting the establishment of international universities. Also explained the problems faced by librarians, problem analysis, solutions, and efforts that must be made to achieve goals in support of international universities.